Path coefficient analysis ovyield and yield components in bread wheat (Triticum aestivum L.) genotypes - Aycicek, Mehmet; Yildirim, Telat (Pakistan Botanical Soc, 2006)
With the trials conducted across two locations and over two years, the correlation coefficients and path analysis were calculated between grain yield and yield components of 20 bread wheat genotypes. Positive and significant correlation was found between yield and plant density, plant height, grain number per spike, grain weight per spike and 1000 kernels weight. Grain yield was negatively and significantly correlated with time to heading. Positive direct effect of plant height and grain weight spike(-1) and negative direct effect of time to heading associated with significant correlation with grain yield suggested that these yield components may be a good selection criteria to improve yield of wheat genotypes.
Keywords: Grain-Yield